IMPLEMENTATION OF SCOUTING ACTIVITIES IN SHAPING THE LEADERSHIP CHARACTER OF STUDENTS AT SMPS IT YPTI SCHOOL - Khairi, Muhammad Aqil; Ridwan, Ahmad; Dahrul (Yayasan Amanah Nur Aman, 2025)
This study examines how the implementation of scouting activities in forming student leadership character at YPTI Lubuk Cemara IT Private Junior High School. This study is a qualitative study with a natural observation research design. This study uses research data acquisition techniques through observation, interviews and documentation. The validity of the data is ensured through triangulation and qualitative data analysis is used to analyze the data, which involves data reduction, presentation and drawing conclusions. The findings in this study indicate that the planning of scouting activities to form leadership character must begin with formulating a clear and structured curriculum, so that the implementation process in schools can run very well and the results of the process can be seen, one of which is the character of student leadership. Further findings in this study indicate that the obstacles faced are inseparable from the motivation and support of various parties, such as support from teachers and especially the lack of support from parents and the next obstacle faced is the lack of facilities and infrastructure. The results of the study indicate that the implementation of scouting activities in forming the character of student leadership at SMP Swasta IT YPTI Lubuk Cemara has been quite effective in fostering student leadership skills. Students who are active in Scouting activities show improvements in leadership aspects such as decision-making skills, responsibility, teamwork, communication skills, self-control, motivational skills.